Pelatihan Optimalisasi Pemasaran Digital Produk Unggulan bagi Pelaku UMKM Perempuan di Desa Geresik - Fitriani, Lili Karmela; Harjadi, Dikdik; Lesmana, Arief Surya; Ningsih, Liya; Firdaus, Galih Adam; Anastasya, Tyas Fitria (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This community service program is expected to optimize digital marketing for flagship products of women-led MSMEs in Geresik Village, Ciawigebang District, Kuningan Regency. The limited understanding of the participants about digital marketing hinders them from increasing their market share and competitiveness in a wider environment. The approach employed was in the form of hands-on mentorship, gifting participants the knowledge and acumen to wield digital tools like social media, online marketplaces, and content creation techniques. The study shows that respondents’ ability to digitally market their products has increased because of the support provided, where more visibility attracts customers and can lead to sales. Some other outcomes or results of the program were collaboration among the MSME sector and the adoption of sustainability in marketing practice. The recommendations go to the sustainability of the program through: establishing a digital community of MSMEs, continuous training, and solidifying ties with government and private stakeholders. This initiative thus illustrates the potential impact of digital marketing for empowering rural MSMEs in support of economic development at the local level.